A Giant Childhood Mesenteric Lipoblastoma With Extensive Maturation - Squillaro, Anthony I.; Chow, Monica D.; Arias, Fernando; Sadimin, Evita T.; Lee, Yi-Horng (Frontiers in Pediatrics, 2020)
Abdominal lipoblastomas are uncommon soft tissue tumors in children and rarely arise from the mesentery. Due to intraabdominal location and slow growth, these masses can go unnoticed for long periods of time and often found on surgical exploration. We present a case of a 12-year-old male with years of abdominal distension accompanied by new onset early satiety that was found to have an intra-abdominal mass. He underwent an exploratory laparotomy revealing a large 33 x 27 x 15 cm rubbery mesenteric mass displacing the entire intra-abdominal contents, connected by a single vascular pedicle and encasing a loop of small intestine. The mass was resected and the patient did well without signs of recurrence. Histology confirmed the presence of mature adipocytes but on further cytogenetic analysis, a translocation between chromosomes 2 and 8 at the 12q arm was detected, which is often associated with lipoblastomas. This case represents the one of the largest mesenteric lipoblastomas that matured extensively to lipoma-like histology at the time of surgical resection.